2016
DOI: 10.1051/0004-6361/201526886
|View full text |Cite
|
Sign up to set email alerts
|

The XXL Survey

Abstract: Context. The XXL Survey is the largest homogeneous survey carried out with XMM-Newton. Covering an area of 50 deg 2 , the survey contains several hundred galaxy clusters out to a redshift of ∼2 above an X-ray flux limit of ∼5 × 10 −15 erg cm −2 s −1 . This paper belongs to the first series of XXL papers focusing on the bright cluster sample. Aims. We investigate the luminosity-temperature (LT) relation for the brightest clusters detected in the XXL Survey, taking fully into account the selection biases. We inv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
105
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 68 publications
21
105
2
Order By: Relevance
“…The stellar content of cluster galaxies and intracluster light generally represents 10−20% of the total baryonic mass (Lin & Mohr 2004;Gonzalez et al 2007;Andreon 2010Andreon , 2015Mulroy et al 2014). The overall baryon content of galaxy clusters is therefore found to be close to the Universal value (Lin et al 2003;Giodini et al 2009;Laganá et al 2013). Interestingly, these studies observed a general trend of increasing gas fraction (Sun et al 2009;Pratt et al 2009;Lovisari et al 2015) and decreasing stellar fraction (e.g.…”
Section: Introductionmentioning
confidence: 90%
“…The stellar content of cluster galaxies and intracluster light generally represents 10−20% of the total baryonic mass (Lin & Mohr 2004;Gonzalez et al 2007;Andreon 2010Andreon , 2015Mulroy et al 2014). The overall baryon content of galaxy clusters is therefore found to be close to the Universal value (Lin et al 2003;Giodini et al 2009;Laganá et al 2013). Interestingly, these studies observed a general trend of increasing gas fraction (Sun et al 2009;Pratt et al 2009;Lovisari et al 2015) and decreasing stellar fraction (e.g.…”
Section: Introductionmentioning
confidence: 90%
“…We adopt a sample of 52 Xray bright clusters selected from the 11 deg 2 XMM-LSS survey region presented in Clerc et al (2014), and also a sample of 51 X-ray bright clusters from the ∼ 25 deg 2 XXL North survey region presented in Pacaud et al (2016) and Giles et al (2016). For both the cluster catalogs, we use X-ray centroids, redshifts from the spectroscopy of member galaxies, X-ray temperatures TX , and rest-frame [0.5-2] keV luminosities within r500,MT, LX,500, where r500,MT is the radius within which the mean matter density of the cluster becomes 500 times the critical density of the Universe at the cluster redshift with the corresponding mass M500 estimated from a mass-temperature relation.…”
Section: X-ray Catalogsmentioning
confidence: 99%
“…, where E(z) = ΩM (1 + z) 3 + ΩΛ, B ∼ 3, and the self-similar model predicts γLT = 1 (e.g., Giles et al 2016). We include the effect of redshift evolution by studying the correlation betweenNmem and evolution-corrected X-ray luminosity [E(z)] −1 LX,500 assuming the self-similar evolution γLT = 1.…”
Section: Correlation Of Richness With X-ray Propertiesmentioning
confidence: 99%
“…Using the surface brightness profile, after removing the PSF of the central AGN, we calculated the flux from the hot ICM in the central region (e.g., within 0.15R500) and outer region (> 0.75R500), and estimate a bolometric luminosity within R500, LX,500, of 2.5 ± 0.4 × 10 44 erg s −1 . Based on the established L − T relation, the estimated luminosity based on the fitted temperature, after correcting for the cosmological evolution term E(z), is ∼ 2.0 × 10 44 erg s −1 from Giles et al (2016), or ∼ 4.2 × 10 44 erg s −1 from Sun (2012).…”
Section: Spectral Analysismentioning
confidence: 99%
“…The gravitational mass is estimated based on the M − T relation (Sun et al 2009). Based on the established L − T relation, the estimated luminosity from the hot ICM, after correcting for the cosmological evolution term E(z), is ∼ 2.0 × 10 44 erg s −1 from Giles et al (2016), or ∼ 4.2 × 10 44 erg s −1 from Sun (2012). b: The fitted radio spectral index across the whole source from 38 MHz to 10 GHz based on the data from NED.…”
Section: Introductionmentioning
confidence: 99%